Culturally informed Strengths-based Coaching: a novel approach to support the success of underrepresented minority faculty - Alli, Julie (Applied Dispute Resolution Journal, 2023)
Underrepresented Minority (URM) faculty play a crucial role in higher education, and yet they face numerous barriers to success. This paper describes a project that seeks to address these barriers by supporting URM faculty through Strengths-based coaching while also examining how social and cultural identities intersect with individual faculty strengths that are determined by the Clifton Strengths online assessment administered by Gallup, Inc. throughout this yearlong intervention, URM junior faculty were paired with senior faculty coaches to provide one-on-one support. Additionally, all faculty participated in a series of workshops aimed at supporting faculty teaching, research, and service by applying individual Strengths through a lens of social/cultural identity. This project serves as a model for how coaching can be used to address an important facet of dispute resolution that involves URM faculty in higher education.